PENGARUH FUNGSI KEPEMIMPINAN TERHADAP PRESTASI KERJA KARYAWAN (Kasus PT. Arara Abadi Distrik Resort Rasau Kuning Perawang) - Ria Damero; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
In a Company having employees may do a good job and may not be good. If an employee has performed responsibly well, then the leader is expected to be responsible as well. To find out the causes there are several possibilities such as whether or not to complete a job assigned and may also not hae the impetus to work well, then it is already one of the leader’s duties to influence employees, in order to work according to company goals.The study aims to determine the effect of leadership functions on employee performance in the case PT. Arara Abadi Rasau Kuning Resort District Perawang, to test the influence of both variables. In the research, the meteology used is descriptive and quantitative in SPSS program, where the sample used is special employees at PT Arara Abadi Rasau Kuning Resort District Perawang, with the census technique method, data received from employees by conducting interviews, questionnaires and literature review.The results of research work performance PT Arara Abadi Rasau Kuning Resort District Perawang, employees have a very good work performance level. However, when viewed from the total score of each dimension of work performance the compensation system dimansion is relatively hiegher. While the dimension of stress level is relatively lower. This means that the company PT Arara Abadi Rasau Kuning Resort District Perawang, needs to lower the employees stress level by holding activities to reduce the stress level of the employees. Based on partial (t-test), it can be concluded that the variables of leadership function have a significant effect on work performance variable.Keywords : leadership function, employee performance, PT. Arara Abadi Rasau Kuning Resort District Perawang.